Leaded aviation gasoline exposure risk and child blood lead levels. Issue 1 (10th January 2023) - Zahran, Sammy; Keyes, Christopher; Lanphear, Bruce
Abstract: Lead-formulated aviation gasoline (avgas) is the primary source of lead emissions in the United States today, consumed by over 170, 000 piston-engine aircraft (PEA). The U.S. Environmental Protection Agency (EPA) estimates that four million people reside within 500m of a PEA-servicing airport. The disposition of avgas around such airports may be an independent source of child lead exposure. We analyze over 14, 000 blood lead samples of children (≤5 y of age) residing near one such airport—Reid-Hillview Airport (RHV) in Santa Clara County, California. Across an ensemble of tests, we find that the blood lead levels (BLLs) of sampled children increase in proximity to RHV, are higher among children east and predominantly downwind of the airport, and increase with the volume of PEA traffic and quantities of avgas sold at the airport. The BLLs of airport-proximate children are especially responsive to an increase in PEA traffic, increasing by about 0.72 μg/dL under periods of maximum PEA traffic. We also observe a significant reduction in child BLLs from a series of pandemic-related interventions in Santa Clara County that contracted PEA traffic at the airport. Finally, we find that children's BLLs increase with measured concentrations of atmospheric lead at the airport. In support of the scientific adjudication of the EPAs recently announced endangerment finding, this in-depth case study indicates that the deposition of avgas significantly elevates the BLLs of at-risk children.